Procesos de desarrollo, conflictos y conservación en la cuenca amazónica: mapeo y análisis de tendencias de investigación - Sierra Baron, Willian (2026)
The Amazon basin faces significant challenges due to resource exploitation, armed conflicts and the need for sustainable development. This paper presents a methodology of thematic review, trend mapping and bibliometric analysis through the analytical tools VOSviewer and RStudio bibliometric package. The information was obtained from the Scopus and Web of Science databases. Sixty-one articles meeting the search criteria were identified. The research trends are oriented to: Socio-environmental and political conflicts and impacts, conservation and community resistance, governance and governability, and extractivist practices. The results of this review provide other researchers with a synthesis of the panorama of studies on the problems of degradation, conservation and socio-political conditions of the Amazon basin that can contribute to the development of policies and future research.